2010
DOI: 10.1088/1751-8113/43/5/055305
|View full text |Cite
|
Sign up to set email alerts
|

Some entanglement features exhibited by two, three and four qubits interacting with an environment in a non-Markovian regime

Abstract: We explore various aspects of the quantum entanglement dynamics of systems of two, three and four qubits interacting with an environment at zero temperature in a non-Markovian regime, as described by the paradigmatic model recently studied by Bellomo, Lo Franco, and Compagno [Bellomo et al. Phys. Rev. Lett. 99 (2007) 160502]. We consider important families of initial states for the alluded systems. The average, typical entanglement evolution associated with each of these families is determined, and its relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 31 publications
(86 reference statements)
3
11
0
Order By: Relevance
“…It transpires from this figure that the finite time intervals of zero entanglement are longer in the case of six qubits than in the case of three qubits. This suggests that the lengths of these intervals tend to increase with the number of qubits, consistently with other results for particular states recently reported in [32]. This trend, however, is not observed when we evaluate the average entanglement evolution corresponding to random initial pure states, as can be appreciated in figure 2.b.…”
Section: B Pure Statessupporting
confidence: 91%
See 2 more Smart Citations
“…It transpires from this figure that the finite time intervals of zero entanglement are longer in the case of six qubits than in the case of three qubits. This suggests that the lengths of these intervals tend to increase with the number of qubits, consistently with other results for particular states recently reported in [32]. This trend, however, is not observed when we evaluate the average entanglement evolution corresponding to random initial pure states, as can be appreciated in figure 2.b.…”
Section: B Pure Statessupporting
confidence: 91%
“…A particularly interesting feature of this process, first pointed out by Zyczkowski and the Horodeckis in a pioneering effort almost ten years ago [21], is that sometimes entanglement vanishes completely in a finite time. This remarkable phenomenon, known as entanglement sudden death (ESD), has been the subject of several theoretical and experimental studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ultimate threat to the reliable practical implementation of quantum technologies base on creation and manipulation of multi-partite entangled states is the phenomenon of decoherence which is due to the unavoidable interaction of the quantum system with its external environment (open quantum system). In fact, such an interaction, independently to the quantum or classical nature of the external environment, is very fatal to the survival of the amount of quantum entanglement between the different constituent parts of a multi-partite quantum system [7,8]. More precisely, the phenomenon of decoherence results in the destruction of the typical quantum properties of the system, such as quantum entanglement and consequently, after a finite interaction time, the state of the system may in some cases undergoes a transition from an entangled to a separable state.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, many different entanglement measures for multi-partite entangled quantum systems defined as the sum of the bipartite entanglement measures over all the possible bi-partitions of total quantum system have been proposed during the years [40,41] (see also the review papers [42,43] and the references therein) and some interesting results based on this strategy have been obtained [44][45][46][47][48][49][50][51][52][53][54][55]. For instance, it has been found that for multi-qubit systems, the degree of entanglement robustness tends to increases or decreases with the increase of the number of qubits of the system [8,56]. In particular, the dynamics of quantum correlations in terms of entanglement and discord in a physical model of three non-interacting qubits subject to a classical environmental noise has recently been investigated [57][58][59].…”
Section: Introductionmentioning
confidence: 99%